2020
DOI: 10.5578/khj.69385
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Accuracy of the CHA2 DS2 -VASc-HSF Score in Determining One-Year Cardiovascular Outcomes in Patients with Non-ST-Elevation Acute Coronary Syndrome: A Retrospective Study

Abstract: Introduction: To investigate the predictive accuracy of the CHA 2 DS 2 -VASc-HSF score in predicting the one-year mortality and major adverse cardiac and cerebrovascular events (MACCEs) in patients with non-STelevation acute coronary syndrome (NSTE-ACS). Patients and Methods:In this retrospective study, the study cohort was divided in to two groups based on the median CHA 2 DS 2 -VASc-HSF score: low-risk group (≤ 4 points) and high-risk group (> 4 points). Results:We enrolled 394 patients with NSTE-ACS (mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In another study, 12 the CHA2DS2-VASc-HSF score was more successful in showing no-reflow phenomenon after PCI in patients with acute coronary syndrome compared with the CHADS2 and CHA2DS2-VASc scores. In addition, Kalyoncuoglu et al 13 found that the CHA2DS2-VASc-HSF score better predicted the 1-year cardiovascular outcomes and major adverse cardiac and cerebrovascular events compared with the CHADS2 and CHADS2-VASc scores in patients with NSTEMI.…”
mentioning
confidence: 99%
“…In another study, 12 the CHA2DS2-VASc-HSF score was more successful in showing no-reflow phenomenon after PCI in patients with acute coronary syndrome compared with the CHADS2 and CHA2DS2-VASc scores. In addition, Kalyoncuoglu et al 13 found that the CHA2DS2-VASc-HSF score better predicted the 1-year cardiovascular outcomes and major adverse cardiac and cerebrovascular events compared with the CHADS2 and CHADS2-VASc scores in patients with NSTEMI.…”
mentioning
confidence: 99%